Analisis Metode Antrian Terhadap Peningkatan Efisiensi dan Efektifitas Pelayanan Laboratorium Klinik Kesehatan pada PT. Prodia Widyahusada - Annatia Kristin Damayanti; Haniza Haniza; Ninny Siregar (JOURNAL OF INDUSTRIAL AND MANUFACTURE ENGINEERING, 2018)
Public awareness about the importance of a medical examination in the laboratory are increase, the more also increased the number of customers in the Clinical Laboratory Health PT. Prodia Widyahusada The influence of queuing method is needed to provide effective and efficient health laboratory service. Queuing method used in the Clinical Laboratory Health PT. Prodia Widyahusada is a service system with Multiple Channel Single Phase System (3/3/1). Service system at the Health Clinic Laboratorium PT. Prodia Widyahusada more better when there is the addition of a service station from three to four service station service station. After the addition of station, the service becomes more effective and efficient, but the evaluation needs to be sustainable because of the level of public awareness about health will continue to increase and needs to be balanced with increased facilities and befter infrastructure.